Two-Component-System RspA1/A2-Dependent Regulation on Primary Metabolism in Streptomyces albus A30 Cultivated With Glutamate as the Sole Nitrogen Source - Zhang, Kuipu; Mohsin, Ali; Yu, Junxiong; Hu, Yuwen; Ali, Muhammad Fahad; Chen, Zhongbing; Zhuang, Yingping; Chu, Ju; Guo, Meijin (Frontiers in Microbiology, 2020)
In our previous study, a two-component-system (TCS) RspA1/A2 was identified and proven to play a positive role in the regulation of salinomycin (antibiotic) biosynthesis in Streptomyces albus. However, the regulatory mechanism of RspA1/A2 using a carbon source (glucose or acetate) for the cell growth of S. albus is still unclear till present research work. Therefore, in this work, the mechanistic pathway of RspA1/A2 on carbon source metabolism is unveiled. Firstly, this work reports that the response regulator RspA1 gene rspA1 knocked-out mutant ΔrspA1 exhibits lower biomass accumulation and lower glucose consumption rates as compared to the parental strain A30 when cultivated in a defined minimal medium (MM) complemented with 75 mM glutamate. Further, it is demonstrated that the regulation of TCS RspA1/A2 on the phosphoenolpyruvate-pyruvate-oxaloacetate node results in decreasing the intracellular acetyl-CoA pool in mutant ΔrspA1. Subsequently, it was verified that the RspA1 could not only directly interact with the promoter regions of key genes encoding AMP-forming acetyl-CoA synthase (ACS), citrate synthase (CS), and pyruvate dehydrogenase complex (PDH) but also bind promoter regions of the genes pyc, pck, and glpX in gluconeogenesis. In addition, the transcriptomic data analysis showed that pyruvate and glutamate transformations supported robust TCS RspA1/A2-dependent regulation of glucose metabolism, which led to a decreased flux of pyruvate into the TCA cycle and an increased flux of gluconeogenesis pathway in mutant ΔrspA1. Finally, a new transcriptional regulatory network of TCS RspA1/A2 on primary metabolism across central carbon metabolic pathways including the glycolysis pathway, TCA cycle, and gluconeogenesis pathway is proposed.